2022
DOI: 10.1021/acsnano.2c02970
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Intrinsic Quantum Confinement in Formamidinium Lead Triiodide Perovskite through Cs Substitution

Abstract: Lead halide perovskites are leading candidates for photovoltaic and light-emitting devices, owing to their excellent and widely tunable optoelectronic properties. Nanostructure control has been central to their development, allowing for improvements in efficiency and stability, and changes in electronic dimensionality. Recently, formamidinium lead triiodide (FAPbI 3 ) has been shown to exhibit intrinsic quantum confinement effects in nominally bulk thin films, apparent through above-band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 86 publications
1
26
0
Order By: Relevance
“…35 Particularly, such defects are expected to be hardly detectable by optical methods at room temperature but they should manifest themselves at low temperatures as a weak blueshifted optical bands in PL and absorption spectra, which could serve as a reasonable explanation of recently reported ''intrinsic quantum confinement'' in FAPbI 3 and FA 1Àx Cs x PbI 3 perovskites. 36,37 On the other hand, repelling charge carriers from the planar defects should impair the charge transport. In addition, as seen from the band diagrams for the considered 9H polytypes (9H(2), 9H(6) and 9H( 5)) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Particularly, such defects are expected to be hardly detectable by optical methods at room temperature but they should manifest themselves at low temperatures as a weak blueshifted optical bands in PL and absorption spectra, which could serve as a reasonable explanation of recently reported ''intrinsic quantum confinement'' in FAPbI 3 and FA 1Àx Cs x PbI 3 perovskites. 36,37 On the other hand, repelling charge carriers from the planar defects should impair the charge transport. In addition, as seen from the band diagrams for the considered 9H polytypes (9H(2), 9H(6) and 9H( 5)) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…35 Particularly, such defects are expected to be hardly detectable by optical methods at room temperature but they should manifest themselves at low temperatures as a weak blue-shifted optical bands in PL and absorption spectra, which could serve as a reasonable explanation of recently reported “intrinsic quantum confinement” in FAPbI 3 and FA 1− x Cs x PbI 3 perovskites. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly though, the relationship between the presence of intrinsic quantum confinement features in the absorption spectra of FAPbI 3 and the performance of photovoltaic devices based on these layers has not yet been examined. Such an investigation is particularly urgent in the context of the myriad of fabrication protocols developed for FAPbI 3 , which currently focus relatively narrowly on elimination of δ-phase features in XRD patterns that has, however, been shown to be an inaccurate indicator , of whether or not intrinsic quantum confinement will be present.…”
mentioning
confidence: 99%
“…We proceeded by probing how the three different fabrication approaches affect the occurrence of intrinsic quantum confinement in FAPbI 3 films. For this purpose, we measured the absorption coefficient spectra at a range of different temperatures from 295 K down to 4 K (displayed in Figure b) in order to determine the fraction of the absorption spectrum that exhibits the peak features that have been associated with such confinement in the past. , While cryogenic temperatures are less relevant to photovoltaic operation, it has recently been shown that they enhance the sharpness and amplitudes of the absorption features, making them easier to discern and evaluate accurately. , To analyze the absorption coefficient spectra, we first fitted the onset with Elliott’s theory, which takes into account the excitonic contribution and Coulombic enhancement to the absorption spectrum , (see dashed lines in Figure b). These fits yielded parameters such as the optical bandgap and exciton binding energy (see SI, Figure 8) that are very similar in both value and temperature trends for the films made through the three fabrication routes, further highlighting that these films are compositionally similar.…”
mentioning
confidence: 99%
“…However, replacing the MA + cation with CH­(NH 2 ) 2 + (FA + ) significantly improves resistance to thermal decomposition. , Unfortunately, neat FAPbI 3 perovskites are also susceptible to structural phase transitions . In particular, the radius of the FA + cation is significantly larger than that of the MA + , which leads to FAPbI 3 being only metastable in its black perovskite α-phase, with its yellow hexagonal δ-phase being thermodynamically favored at room temperature . However, alloying FA + with Cs + (which has a smaller cation radius) forms the stable FA 1– x Cs x PbI 3 in its perovskite α-phase for a range of alloy fractions from x = 0.1 to x = 0.5. , Nevertheless, there are only a few reports of vacuum codeposition of such multication FACs-based perovskites. ,,,, …”
Section: Introductionmentioning
confidence: 99%